Perlindungan Hukum Korban Kekerasan dalam Rumah Tangga - Rahma, Andi (Al-Daulah : Journal of Criminal Law and State Administration Law, 2013)
Problems of fundamental which is told in this research is how protection of law to Woman Of Victim Doing An Injustice Hardness In Household In town of Makassar, and Factor influencing protection of law to woman of victim to hardness doing an injustice in household.Method the used is approach of sosioyuridis and nature of research is descriptive, in this research which become population is Makassar polrestabes, public attorney of Country of Makassar, district court, office institute legal aid, housemaid employer and victim reside in town of Makassar, there is research sampel specified by purpossive sampling. Data collecting  by  documentation and interview.  obtained  data  is hereinafter analysed qualitative that is analysis having the character of mendersripsikan.Result of this research indicate that protection of law to woman of hardness doing an injustice victim in household after going into effect law  it of No 23 Year 2004 not yet been conducted maximally. Although from  3 hardness case to pemabantu of reported household to police, its of him use law assertion of No23 Year 2004. But existing peripherals not yet walked better.Hardness victim which there is still do not report hardness to role x'self and also society realized by way of change of protection  ascription  is  an  work  of  excellency  of  daan  if knowing the happening of hardness of vinicity environment  to be is immediately reported. Factor influencing protection of law to woman of victim to hardness doing an injustice in household. that is by preventif (pencegahan) handled by Bimnas (Tuition Society). While duties of Represif (penindakan of law) executed by part of police detective. Governmental deservedly give attention  to  more   to   housemaid   by   way   of  forming   an regulation of prundang-undangan arranging it.